Fiber and method for producing fiber

By using hydrogenated block copolymers specified in structure and flowability in the fibers, the shortcomings of existing fibers in terms of strength characteristics, rotational properties and low stress recovery are solved, and the excellent properties of the fibers are achieved.

JP2025062188APending Publication Date: 2025-04-14ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023171083
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-02
Publication Date
2025-04-14

AI Technical Summary

Technical Problem

There is still room for improvement in existing fibers in terms of strength characteristics, rotational properties and low stress recovery.

Method used

Fibers containing hydrogenated block copolymers are used, with the structure and flowability (MFR) specified within the appropriate range to obtain excellent strength characteristics, rotational properties and low stress recovery.

Benefits of technology

The excellent strength characteristics, rotational properties and low stress recovery of the fiber are achieved, and the overall performance of the fiber is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062188000001
    Figure 2025062188000001
  • Figure 2025062188000002
    Figure 2025062188000002
  • Figure 2025062188000003
    Figure 2025062188000003
Patent Text Reader

Abstract

To provide a method for producing a fiber that enables obtaining a fiber excellent in strength characteristics, spinnability, and low-stress recoverability.SOLUTION: The fiber comprises a hydrogenated block copolymer (i) satisfying the following conditions 1 to 4. The hydrogenated block copolymer (i) is a hydrogenated product of a block copolymer containing a vinyl aromatic monomer unit and a conjugated diene monomer unit (condition 1). The hydrogenated block copolymer (i) contains at least one polymer block (a) mainly composed of the vinyl aromatic monomer unit, and a content of the polymer block (a) in (i) is 10 mass% or more (condition 2). The hydrogenated block copolymer (i) contains at least one hydrogenated copolymer block (b) composed of the vinyl aromatic monomer unit and the conjugated diene monomer unit, and a content of the vinyl aromatic monomer unit in (b) is 5 to 79 mass% (condition 3). The hydrogenated block copolymer (i) has a MFR value of 10 or more under conditions of 230°C and a load of 2.16 kg according to JIS K7210 (condition 4).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to fibers and methods for making fibers. [Background technology]

[0002] 2. Description of the Related Art Conventionally, fibers for use in clothing and interior products have been required to have good texture, excellent durability such as abrasion resistance and scratch resistance, high impact absorption, and the ability to be lightweight.

[0003] For example, Patent Document 1 discloses a resin composition that can be melt-spun by mixing a specific triblock copolymer and a specific diblock copolymer. However, the fiber made of this resin composition has a problem that the strength decreases as the blending amount of the diblock copolymer increases.

[0004] Patent Document 2 discloses a fiber made of a styrene-based elastomer having a styrene-butadiene-isoprene structure, which has excellent solvent resistance, flexibility, excellent low-temperature properties, high strength, and good elastic properties. However, this styrene-based elastomer has problems in that there are still areas that need improvement in terms of spinnability and low stress recovery. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 62-33818 [Patent Document 2] Japanese Patent Application Publication No. 6-57525 Summary of the Invention [Problem to be solved by the invention]

[0006] As described above, the fibers proposed so far have problems in that there is still room for improvement in terms of strength characteristics, spinnability, and low stress recovery.

[0007] Therefore, an object of the present invention is to provide a fiber having excellent strength properties, spinnability, and low stress recovery properties. [Means for solving the problem]

[0008] Means for Solving the Problems of the Prior Art The present inventors have conducted intensive research to solve the problems of the prior art described above, and as a result have found that, in a fiber containing a hydrogenated block copolymer, by specifying the structure and MFR of the hydrogenated block copolymer within appropriate ranges, a fiber excellent in strength characteristics, spinnability, and low stress recovery properties can be obtained, thereby completing the present invention. That is, the present invention is as follows.

[0009] [1] A fiber containing a hydrogenated block copolymer (a) that satisfies the following conditions (1) to (4): <Condition (1)>: The hydrogenated block copolymer (a) is a hydrogenated product of a block copolymer containing vinyl aromatic monomer units and conjugated diene monomer units. <Condition (2)>: The hydrogenated block copolymer (i) contains at least one polymer block (a) mainly composed of a vinyl aromatic monomer unit, The content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (i) is 10% by mass or more. <Condition (3)>: The hydrogenated block copolymer (a) contains at least one hydrogenated copolymer block (b) composed of a vinyl aromatic monomer unit and a conjugated diene monomer unit, The content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is from 5% by mass to 79% by mass. <Condition (4)>: The hydrogenated block copolymer (a) has an MFR value of 10 or more, measured according to JIS K7210 at a temperature of 230° C. and a load of 2.16 kg. [2] The fiber according to [1] above, having a total fineness of 10 dtex or more and 500 dtex or less. [3] The fiber according to the above [1] or [2], wherein the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is 45% by mass or more and 79% by mass or less. [4] The fiber according to any one of [1] to [3], wherein the content of the polymer block (a) mainly composed of the vinyl aromatic monomer unit in the hydrogenated block copolymer (i) is 15% by mass or more and 40% by mass or less. [5] The fiber according to any one of [1] to [4] above, wherein the hydrogenated block copolymer (i) has an MFR value of 50 or more measured under conditions of a temperature of 230° C. and a load of 2.16 kg according to JIS K7210. [6] The fiber according to any one of [1] to [5], wherein the hydrogenated block copolymer (i) has an instantaneous hardness of 60 or more as measured with a durometer type A according to JIS K6253 and an instantaneous hardness of 50 or less as measured with a durometer type D according to JIS K6253. [7] The fiber is The fiber according to any one of [1] to [6] above, which is a fiber for any application selected from the group consisting of sportswear and cushioning. [8] A method for producing a fiber according to any one of [1] to [7], The hydrogenated block copolymer (a) is melted, extruded from a spinneret of an extruder having a spinneret, and spun while being cooled with cold air. A method for producing fibers. Effect of the Invention

[0010] According to the present invention, fibers having excellent strength properties, spinnability, and low stress recovery properties can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment for carrying out the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and is not intended to limit the present invention to the following content, and the present invention can be carried out in various modifications within the scope of the gist of the present invention.

[0012] 〔fiber〕 The fiber of the present embodiment contains a hydrogenated block copolymer (a) that satisfies the following conditions (1) to (4). <Condition (1)>: The hydrogenated block copolymer (a) is a hydrogenated product of a block copolymer containing vinyl aromatic monomer units and conjugated diene monomer units. <Condition (2)>: The hydrogenated block copolymer (i) contains at least one polymer block (a) mainly composed of a vinyl aromatic monomer unit, The content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (i) is 10% by mass or more. <Condition (3)>: The hydrogenated block copolymer (a) contains at least one hydrogenated copolymer block (b) composed of a vinyl aromatic monomer unit and a conjugated diene monomer unit, The content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is from 5% by mass to 79% by mass. <Condition (4)>: The hydrogenated block copolymer (a) has an MFR value of 10 or more, measured according to JIS K7210 at a temperature of 230° C. and a load of 2.16 kg.

[0013] According to the above-mentioned constitution, a fiber having excellent strength characteristics, spinnability, and low stress recovery property can be obtained.

[0014] (Hydrogenated block copolymer (A)) The hydrogenated block copolymer (a) used in the fiber of the present embodiment is a hydrogenated product of a block copolymer containing vinyl aromatic monomer units and conjugated diene monomer units (the above-mentioned condition (1)).

[0015] <Vinyl aromatic monomer unit> Examples of vinyl aromatic compounds that form vinyl aromatic monomer units include, but are not limited to, monomer units derived from styrene, α-methylstyrene, p-methylstyrene, divinylbenzene, 1,1-diphenylethylene, N,N-dimethyl-p-aminoethylstyrene, N,N-diethyl-p-aminoethylstyrene, and the like. In particular, styrene is preferred from the viewpoint of the balance between the cost and the mechanical strength of the fiber containing the hydrogenated block copolymer (a). These may be used alone or in combination of two or more.

[0016] <Conjugated diene monomer unit> A conjugated diene monomer unit is a monomer unit derived from a diolefin having a pair of conjugated double bonds. Examples of such diolefins include, but are not limited to, 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, and 1,3-hexadiene. In particular, 1,3-butadiene and isoprene are preferred from the viewpoint of a good balance between moldability and mechanical strength. These may be used alone or in combination of two or more.

[0017] In this specification, in the composition of the hydrogenated block copolymer (a), the term "mainly composed of" means that the proportion in a specific block polymer or polymer block is 85 mass % or more, preferably 90 mass % or more, and more preferably 95 mass % or more. In addition, since the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is 5% by mass or more and 79% by mass or less (the above-mentioned condition (3)), the polymer block (a) and the hydrogenated copolymer block (b) can be clearly distinguished from each other.

[0018] <Amount of vinyl bonds in all conjugated diene monomer units> The amount of vinyl bonds in all conjugated diene monomer units of the hydrogenated block copolymer (a) is not particularly limited, but is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 15% by mass or more. Also, it is preferably 80% by mass or less, more preferably 75% by mass or less, and further preferably 70% by mass or less. In this specification, the term "vinyl bond amount" refers to the total amount of conjugated diene monomer units bonded with 1,2-vinyl bonds (conjugated dienes incorporated into a polymer via 1,2-bonds) and 3,4-vinyl bonds (conjugated dienes incorporated into a polymer via 3,4-bonds) relative to the total conjugated dienes (however, when 1,3-butadiene is used as the conjugated diene, the 1,2-vinyl bond amount) and includes the state in which the 1,2-vinyl bond or the 3,4-vinyl bond is subsequently hydrogenated to become a single bond. In other words, although "vinyl" is a name that indicates the state of a double bond, the "vinyl bond amount" in this specification includes the amount of bonds in which the vinyl bond is hydrogenated to become a single bond. When measured in the production process of a hydrogenated block copolymer, the total amount of 1,2-vinyl bonds and 3,4-vinyl bonds relative to the total conjugated dienes measured before the hydrogenation process corresponds to the "vinyl bond amount". When the amount of vinyl bonds in all conjugated diene monomer units of the hydrogenated block copolymer (a) is 5% by mass or more, precipitation from the solution due to crystallization of the hydrogenated conjugated diene block can be suppressed in the hydrogenation step. Furthermore, when the amount of vinyl bonds in all conjugated diene monomer units of the hydrogenated block copolymer (a) is 5% by mass or more, good spinnability is exhibited. When the amount of vinyl bonds in all conjugated diene monomer units of the hydrogenated block copolymer (a) is 80 mass % or less, it is possible to obtain fibers having good resistance to heat deterioration. When the amount of vinyl bonds in all conjugated diene monomer units of the hydrogenated block copolymer (a) is 80 mass % or less, the stickiness is reduced, and fibers having a good touch can be obtained. The vinyl bond amount in all conjugated diene monomer units of the hydrogenated block copolymer (a) can be controlled within the above numerical range by using a regulator such as a tertiary amine compound or an ether compound described later. The amount of vinyl bonds in all conjugated diene monomer units of the hydrogenated block copolymer (a) can be measured by nuclear magnetic resonance (NMR) using the block copolymer before hydrogenation as a sample, or by an infrared spectrophotometer as described in the Examples below. Furthermore, in the measurement by nuclear magnetic resonance (NMR) using the hydrogenated block copolymer as a sample, the amount of vinyl bonds can be calculated by counting the total number of structures that have been hydrogenated into single bonds in addition to unhydrogenated vinyl structures.

[0019] <Total vinyl aromatic compound content> The hydrogenated block copolymer (i) preferably has a total vinyl aromatic monomer unit content of 50% by mass or more and 80% by mass or less, more preferably 55% by mass or more and 80% by mass or less, and even more preferably 60% by mass or more and 80% by mass or less. When the content of all vinyl aromatic monomer units is 50% by mass or more, the hydrogenated block copolymer (A) tends to have good oil resistance. When the oil resistance is good, it can be used in applications requiring stricter oil resistance, such as automotive materials. For example, when the fiber of the present embodiment is used in automotive interior materials, it tends to be possible to suppress deformation and poor appearance even after long-term use. The total vinyl aromatic monomer unit content in the hydrogenated block copolymer (a) can be measured using an ultraviolet spectrophotometer with the block copolymer before hydrogenation and the hydrogenated block copolymer after hydrogenation as samples. The total content of vinyl aromatic monomer units in the hydrogenated block copolymer (a) can be controlled within the above-mentioned numerical range mainly by adjusting the amount of vinyl aromatic compound added to the polymerization reactor, the reaction temperature and the reaction time.

[0020] <Polymer block (a) mainly composed of vinyl aromatic monomer units> The hydrogenated block copolymer (i) used in the fiber of this embodiment contains at least one polymer block (a) mainly composed of vinyl aromatic monomer units (the above-mentioned condition (2)). This makes it possible to prevent pellet blocking. Moreover, the content of the polymer block (a) in the hydrogenated block copolymer (i) is 10% by mass or more, preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more, from the viewpoint of spinnability. When the content of the polymer block (a) mainly composed of vinyl aromatic monomer units is 10% by mass or more, a high solidification rate can be achieved in the process of spinning the hydrogenated block copolymer (a) into fiber, and a lightweight fiber with a low total fineness can be produced at high speed. In addition, the blocking resistance of the pellets of the hydrogenated block copolymer (a) becomes good, and the fiber of this embodiment tends to exhibit excellent abrasion resistance and heat resistance.

[0021] If the pellets of hydrogenated block copolymer (A) show good blocking resistance, blocking is less likely to occur even under conditions such as longer periods of transportation, higher loads, and severe temperature environments (e.g., areas with high outside temperatures and areas with large temperature differences), and it is expected that pellet measurement and blending during compound molding will be made easier. In addition, since the amount of anti-blocking agent can be reduced, it is expected that the effects of avoiding equipment contamination, reducing environmental load, and suppressing unexpected deterioration of physical properties, such as deterioration of transparency and mechanical strength, can be suppressed. Furthermore, when the hydrogenated block copolymer (a) has good spinnability, a high solidification rate can be achieved in the fiber formation process, and even when the total fineness is reduced, a lightweight fiber having sufficient strength for practical use can be produced. When the fiber of the present embodiment shows good abrasion resistance, it can be used in applications requiring stricter abrasion resistance, such as automobile interior materials using the fiber of the present embodiment. For example, in the case of cushions, which are automobile interior materials, the appearance of the material can be expected to be maintained even when used for a long period of time. In addition, when assuming riding in a car, even when the material is subjected to friction with a higher load or a coarser fabric, such as jeans fabric, which is a coarser fabric than cotton fabric such as Kanakin No. 3, the appearance of the material can be expected to be maintained for a long period of time.

[0022] Furthermore, the hydrogenated block copolymer (i) preferably has a polymer block (a) content of 40 mass % or less, more preferably 38 mass % or less, even more preferably 36 mass % or less, and even more preferably 35 mass % or less. When the content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (i) is 40% by mass or less, from the viewpoint of improving the texture of various materials using the fiber of the present embodiment, the above tends to be expressed, and when the content is 35% by mass or less, an even better texture tends to be expressed.

[0023] The content of polymer block (a) in the hydrogenated block copolymer (i) can be measured by a method using a nuclear magnetic resonance (NMR) apparatus (the method described in Y. Tanaka, et al., RUBBER CHEMISTRY and TECHNOLOGY 54, 685 (1981), hereinafter referred to as the "NMR method") using the block copolymer before hydrogenation and the hydrogenated block copolymer after hydrogenation as samples. The content of the polymer block (a) in the hydrogenated block copolymer (i) can be controlled within the above-mentioned numerical range mainly by adjusting the amount of the vinyl aromatic compound added to the polymerization reactor, the reaction temperature and the reaction time.

[0024] <Hydrogenated copolymer block (b)> The hydrogenated block copolymer (i) used in the fiber of this embodiment contains at least one hydrogenated copolymer block (b) composed of a vinyl aromatic monomer unit and a conjugated diene monomer unit. The content of the vinyl aromatic monomer unit in the hydrogenated copolymer block (b) is 5% by mass or more, preferably 15% by mass or more, more preferably 30% by mass or more, and even more preferably 45% by mass or more. When the content of vinyl aromatic monomer unit in hydrogenated copolymer block (b) is 5% by mass or more, the fiber of this embodiment exhibits good abrasion resistance.Furthermore, when the content is 45% by mass or more, higher abrasion resistance is exhibited, and it can be used in applications where abrasion resistance is more stringent, such as automobile interior materials, thin woven fabrics and nonwoven fabrics, and automobile interior materials that require long-term appearance maintenance under friction caused by higher loads and coarse fabrics, such as jeans fabrics, which are coarser than cotton fabrics such as Kanakin No. 3, when riding in the vehicle. In addition, when the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is 5% by mass or more, the fiber of this embodiment exhibits excellent low stress recovery, and in clothing applications (sportswear, underwear, general clothing such as jeans, etc.), the tightness when worn is alleviated, improving comfort. In addition, in the seat of a car or a chair, the fit to the waist when sitting is improved, improving comfort. Furthermore, when the content is 45% by mass or more, even higher comfort can be obtained. Furthermore, when the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is 5% by mass or more, the fiber of this embodiment exhibits excellent vibration absorption properties, and when used in clothing (sportswear, underwear, general clothing such as jeans, etc.), it absorbs the shaking of muscles and breasts, etc., and reduces fatigue. When used as a protective material for electronic devices, etc., it prevents damage to the devices due to vibration. Furthermore, when the content is 45% by mass or more, even higher vibration absorption properties can be obtained. The content of the hydrogenated copolymer block (b) in the hydrogenated block copolymer (a) is not particularly limited, but is preferably 40% by mass or more, more preferably 45% by mass or more, and more preferably 50% by mass or more. When the content of the hydrogenated copolymer block (b) in the hydrogenated block copolymer (a) of this embodiment is 40% by mass or more, the fiber of this embodiment exhibits excellent low stress recovery properties.

[0025] The content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is 79% by mass or less, preferably 75% by mass or less, and more preferably 70% by mass or less. When the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is 79% by mass or less, the fiber of the present embodiment exhibits good heat resistance [high temperature C-Set (compression set)] and can be used in applications where strict heat resistance is required, such as applications for making thinner woven fabrics and nonwoven fabrics in automobile interior materials, and applications where resistance is required to maintain the texture (grained texture) and shape (resistance to deformation due to heat) of the material for a long period of time even when used for a long period of time or at higher temperatures. Furthermore, when the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is 79% by mass or less, the fiber of the present embodiment exhibits good tensile strength and elongation.

[0026] The content of the vinyl aromatic monomer unit in the hydrogenated copolymer block (b) can be measured by a nuclear magnetic resonance (NMR) spectrometer or the like. The content of the vinyl aromatic monomer unit in the hydrogenated copolymer block (b) can be controlled within the above-mentioned numerical range by adjusting the amounts of the vinyl aromatic compound and conjugated diene added to the polymerization reactor, the reaction temperature, etc.

[0027] <Weight average molecular weight of hydrogenated block copolymer (a)> The hydrogenated block copolymer (A) used in the fiber of the present embodiment has a weight average molecular weight (Mw) of preferably 10,000 or more, more preferably 30,000 or more, and even more preferably 50,000 or more, from the viewpoints of extrusion moldability during pellet production of the hydrogenated block copolymer (A) and of obtaining good mechanical strength and low stickiness in the fiber of the present embodiment. The upper limit is preferably 300,000 or less, more preferably 200,000 or less, and even more preferably 150,000 or less. When the weight average molecular weight (Mw) is 300,000 or less, the hydrogenated block copolymer (A) tends to be easily melted during pellet production (extrusion molding) of the hydrogenated block copolymer (A), the strands tend to be stabilized, and the extrusion moldability tends to be improved. The weight average molecular weight of the hydrogenated block copolymer (a) is determined by measuring with gel permeation chromatography (GPC) and using a calibration curve (created using the peak molecular weight of the standard polystyrene) obtained from the measurement of commercially available standard polystyrene.

[0028] <Molecular weight distribution (Mw / Mn) of hydrogenated block copolymer (a)> The hydrogenated block copolymer (a) used for the fiber of the present embodiment is not particularly limited in molecular weight distribution (Mw / Mn), but from the viewpoint of processability, it is preferably 10 or less, more preferably 3 or less, and even more preferably 1.5 or less. From the viewpoint of processability, the lower limit of Mw / Mn is preferably 1 or more, more preferably 1.005 or more, and even more preferably 1.01 or more. The weight average molecular weight (Mw) and number average molecular weight (Mn) of the hydrogenated block copolymer (A) are measured by gel permeation chromatography (GPC), and the molecular weight of the peak of the chromatogram is determined using a calibration curve (created using the peak molecular weight of the standard polystyrene) obtained by measuring a commercially available standard polystyrene. The molecular weight distribution (Mw / Mn) of the hydrogenated block copolymer (A) is determined from the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn).

[0029] <Hydrogenation rate of double bonds of conjugated diene monomer units in hydrogenated block copolymer (a)> The hydrogenation rate of the double bonds of the conjugated diene monomer units in the hydrogenated block copolymer (i) used for the fiber of this embodiment is preferably 80% or more, more preferably 85% or more, and even more preferably 92% or more, from the viewpoint of obtaining good weather resistance. In particular, in applications such as automobile interior materials and clothing, high abrasion resistance and weather resistance are required, so the hydrogenation rate tends to be preferably 92% or more. The hydrogenation rate of the double bonds of the conjugated diene monomer units in the hydrogenated block copolymer (A) can be controlled to the above-mentioned numerical range by adjusting the amount of hydrogenation. The hydrogenation rate of the hydrogenated block copolymer (A) can be measured using a nuclear magnetic resonance (NMR) spectrometer or the like.

[0030] <Structure of hydrogenated block copolymer (a)> The hydrogenated block copolymer (a) used in the fiber of the present embodiment is not particularly limited, but examples thereof include those having a structure represented by the following general formula.

[0031] aba, (ab) n -X, In each of the above general formulas, a represents a polymer block (a) mainly composed of vinyl aromatic monomer units, and b represents a hydrogenated copolymer block (b) composed of vinyl aromatic monomer units and conjugated diene monomer units. n is an integer of 1 or more, and preferably an integer of 1 to 5. m is an integer of 2 or more, and preferably an integer of 2-11. X represents a residue of a coupling agent or a residue of a multifunctional initiator.

[0032] The hydrogenated block copolymer (A) used in the fiber of this embodiment may be a modified block copolymer to which an atomic group having a specific functional group is bonded. Since the presence or absence of a functional group has little effect on the hardness and / or MFR of the hydrogenated block copolymer (A), the presence or absence of modification and the type of functional group may be appropriately determined depending on the structure of the resin to be kneaded, etc. In addition, when the hydrogenated block copolymer (a) is a modified block copolymer, it may be a secondary modified block copolymer. In this specification, "secondary modification" is a name characterized by the manufacturing method, and the first step of bonding a functional group to a block copolymer is called primary modification, and the step of reacting the functional group with another compound is called secondary modification. For example, a typical manufacturing method is to polymerize in a solution, and then react a modifier (e.g., amine) at the polymerization end terminal of the primary modified product with another compound (e.g., maleic acid) in an extruder to produce a secondary modified product.

[0033] <MFR of hydrogenated block copolymer (a)> The hydrogenated block copolymer (a) used in the fiber of this embodiment has an MFR value of 10 or more, preferably 20 or more, and more preferably 50 or more, measured according to JIS K7210 at a temperature of 230° C. and a load of 2.16 kg. When the hydrogenated block copolymer (a) has an MFR of 10 or more, good processability is exhibited. When the hydrogenated block copolymer (a) has good processability, an extruder having a smaller spinneret can be used in the production process of the fiber of this embodiment, and good spinnability can be obtained, resulting in a fiber having a preferred total fineness described below and excellent low stress recovery and strength properties. The upper limit of the MFR of the hydrogenated block copolymer (a) is not particularly limited, but from the viewpoint of maintaining heat resistance, it is preferably 500 or less, and more preferably 250 or less. By setting the MFR of the hydrogenated block copolymer (a) within the above-mentioned numerical range, the spinnability becomes good, and the total fineness of the fiber of the present embodiment can be controlled within the range of 10 dtex or more and 500 dtex or less, and a fiber that is lightweight and has sufficient strength for practical use can be obtained.

[0034] The MFR of the hydrogenated block copolymer (i) can be controlled within the above-mentioned numerical range by adjusting the weight average molecular weight of the hydrogenated block copolymer (i), the content of polymer block (a), the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b), the content of hydrogenated polymer block (c), the amount of vinyl bonds in the conjugated diene monomer units of the hydrogenated block copolymer (i) before hydrogenation, and the hydrogenation rate of the double bonds in the conjugated diene monomer units of the hydrogenated block copolymer (i). For example, the MFR of the hydrogenated block copolymer (a) tends to be improved by reducing the weight average molecular weight of the hydrogenated block copolymer (a), reducing the content of polymer block (a), increasing the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b), increasing the content of hydrogenated polymer block (c) in the terminal blocks, reducing the content of hydrogenated polymer block (c) in the internal blocks, increasing the amount of vinyl bonds in the conjugated diene monomer units, and reducing the hydrogenation rate of double bonds in the conjugated diene monomer units. In particular, the weight average molecular weight of the hydrogenated block copolymer (a) is linearly related to the logarithm of MFR. Therefore, in order to obtain the hydrogenated block copolymer (a) that exhibits the effects of the present invention, the content of the polymer block (a), the content of the vinyl aromatic monomer unit in the hydrogenated copolymer block (b), and the hardness of the hydrogenated block copolymer (a) are adjusted so that the blocking resistance of the pellets, the heat resistance, and the abrasion resistance of the hydrogenated block copolymer (a) are exhibited, and then the weight average molecular weight that gives the desired MFR can be determined from the linear relationship between the weight average molecular weight of the hydrogenated block copolymer (a) and the logarithm of MFR.

[0035] <Hardness of hydrogenated block copolymer (a)> The hydrogenated block copolymer (a) preferably has an instantaneous hardness measured with a durometer type A in accordance with JIS K6253 of 60 or more, more preferably 65 or more, even more preferably 70 or more, and even more preferably 80 or more, from the viewpoint of spinnability. When the hydrogenated block copolymer (A) has an instantaneous hardness of 60 or more as measured with a durometer type A according to JIS K6253, or a durometer type D measurement value of 16 or more, the hydrogenated block copolymer (A) has good spinnability. When the hydrogenated block copolymer (a) has good spinnability, the total fineness of the fiber of this embodiment can be controlled within a suitable numerical range, and a fiber that is lightweight and has sufficient strength for practical use can be obtained.

[0036] The instantaneous hardness of the hydrogenated block copolymer (a), as measured with a durometer type D according to JIS K6253, is preferably 65 or less, more preferably 55 or less, and even more preferably 50 or less, from the viewpoint of improving the feel of various materials using the fiber of this embodiment. When the hydrogenated block copolymer (a) has an instantaneous hardness of 65 or less as measured with a durometer type D according to JIS K6253, a good feel can be obtained when the fiber of this embodiment is used. If the fiber of this embodiment has a good texture, when it is used as an automobile interior material or the like, a luxurious feel such as leather-like texture and warmth can be obtained, and higher product value can be achieved.

[0037] The hardness of the hydrogenated block copolymer (a) can be controlled within the above-mentioned numerical range by adjusting the weight average molecular weight of the hydrogenated block copolymer (a), the content of the polymer block (a), the content of the vinyl aromatic monomer unit in the hydrogenated copolymer block (b), the content of the hydrogenated polymer block (c), the amount of vinyl bonds in the conjugated diene monomer units, and the hydrogenation rate of the double bonds in the conjugated diene monomer units. Furthermore, the hardness may be controlled within the above-mentioned numerical range by adjusting the tan δ peak temperature (loss tangent) from −25° C. to 60° C. in the viscoelasticity measurement chart of the hydrogenated block copolymer (a), i.e., the glass transition temperature derived from the hydrogenated copolymer block (b), by carrying out a polymerization reaction under the conditions described below using a predetermined regulator that adjusts the vinyl bond amount in the hydrogenated copolymer block (b), the content of the vinyl aromatic monomer unit in the hydrogenated copolymer block (b), and the copolymerizability between the vinyl aromatic compound and the conjugated diene. For example, the hardness of the hydrogenated block copolymer (a) is improved by increasing the content of the polymer block (a) in the hydrogenated block copolymer (a), increasing the content of the vinyl aromatic monomer unit in the hydrogenated copolymer block (b), decreasing the content of the hydrogenated polymer block (c), decreasing the hydrogenation rate of the double bond of the conjugated diene monomer unit, and increasing the tan δ peak temperature (°C) from -20°C to 60°C. In order to improve the tan δ peak temperature (°C) from -20°C to 60°C, it is particularly effective to increase the content of the vinyl aromatic monomer unit in the hydrogenated copolymer block (b) and to increase the amount of vinyl bonds in the hydrogenated copolymer block (b). The tan δ peak temperature (°C) can also be controlled by adjusting the copolymerizability of the vinyl aromatic compound and the conjugated diene by adjusting the polymerization conditions described below.

[0038] (Production method of hydrogenated block copolymer (a)) The hydrogenated block copolymer (a) used in the fiber of the present embodiment, which is in a state before hydrogenation, can be obtained, for example, by carrying out living anionic polymerization of a vinyl aromatic compound and a conjugated diene compound in a hydrocarbon solvent using a polymerization initiator such as an organic alkali metal compound.

[0039] <Hydrocarbon solvent> Examples of hydrocarbon solvents include, but are not limited to, aliphatic hydrocarbons such as n-butane, isobutane, n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclohexane, cycloheptane, and methylcycloheptane; and aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene.

[0040] <Polymerization initiator> The polymerization initiator is not particularly limited, but examples thereof include organic alkali metal compounds such as aliphatic hydrocarbon alkali metal compounds, aromatic hydrocarbon alkali metal compounds, and organic amino alkali metal compounds, which are known to have anionic polymerization activity toward vinyl aromatic compounds and conjugated dienes. The organic alkali metal compound is not limited to the following, but for example, an aliphatic or aromatic hydrocarbon lithium compound having 1 to 20 carbon atoms is preferable, and a compound containing one lithium atom in one molecule, a dilithium compound containing multiple lithium atoms in one molecule, a trilithium compound, or a tetralithium compound can be used. Specific examples include n-propyllithium, n-butyllithium, sec-butyllithium, tert-butyllithium, n-pentyllithium, n-hexyllithium, benzyllithium, phenyllithium, tolyllithium, a reaction product of diisopropenylbenzene with sec-butyllithium, and a reaction product of divinylbenzene with sec-butyllithium and a small amount of 1,3-butadiene. Furthermore, for example, the organic alkali metal compounds disclosed in US Pat. No. 5,708,092, British Patent No. 2,241,239, and US Pat. No. 5,527,753 can also be used.

[0041] <Adjustment agent> When an organic alkali metal compound is used as a polymerization initiator to copolymerize a vinyl aromatic compound with a conjugated diene, the content of vinyl bonds (1,2-bonds or 3,4-bonds) resulting from the conjugated diene incorporated in the polymer and the random copolymerizability of the vinyl aromatic compound with the conjugated diene can be adjusted by using a specific regulator. Such regulators include, but are not limited to, tertiary amine compounds, ether compounds, metal alcoholate compounds, and the like. The regulator may be used alone or in combination of two or more kinds.

[0042] Examples of tertiary amine compounds include, but are not limited to, compounds represented by the general formula: R1R2R3N (wherein R1, R2, and R3 each represent a hydrocarbon group having 1 to 20 carbon atoms or a hydrocarbon group having a tertiary amino group). Specific examples include trimethylamine, triethylamine, tributylamine, N,N-dimethylaniline, N-ethylpiperidine, N-methylpyrrolidine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, 1,2-dipiperidinoethane, trimethylaminoethylpiperazine, N,N,N',N",N"-pentamethylethylenetriamine, and N,N'-dioctyl-p-phenylenediamine.

[0043] The ether compound is not limited to the following, but for example, a linear ether compound and a cyclic ether compound can be used. Examples of linear ether compounds include, but are not limited to, dialkyl ether compounds of ethylene glycol, such as dimethyl ether, diethyl ether, diphenyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and ethylene glycol dibutyl ether, and dialkyl ether compounds of diethylene glycol, such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, and diethylene glycol dibutyl ether. Examples of cyclic ether compounds include, but are not limited to, tetrahydrofuran, dioxane, 2,5-dimethyloxolane, 2,2,5,5-tetramethyloxolane, 2,2-bis(2-oxolanyl)propane, and alkyl ethers of furfuryl alcohol.

[0044] Examples of the metal alcoholate compound include, but are not limited to, sodium t-pentoxide, sodium t-butoxide, potassium t-pentoxide, potassium t-butoxide, and the like.

[0045] <Polymerization method> As a method for polymerizing a vinyl aromatic compound and a conjugated diene using an organic alkali metal compound as a polymerization initiator, a conventionally known method can be applied. Although not limited thereto, for example, any of batch polymerization, continuous polymerization, and a combination of these may be used, with batch polymerization being particularly suitable for obtaining a copolymer having excellent heat resistance. The polymerization temperature is preferably from 0° C. to 180° C., more preferably from 30° C. to 150° C. The polymerization time varies depending on the conditions, but is usually within 48 hours, preferably from 0.1 to 10 hours. The polymerization atmosphere is preferably an inert gas atmosphere such as nitrogen gas. The polymerization pressure is not particularly limited as long as it is set within a pressure range that allows the monomer and the solvent to be maintained in a liquid phase within the above-mentioned temperature range. Furthermore, it is preferable to take care not to introduce impurities such as water, oxygen, carbon dioxide gas, etc., which may inactivate the catalyst and the living polymer, into the polymerization system.

[0046] Furthermore, at the end of the polymerization step, a required amount of a bifunctional or higher functional coupling agent may be added to carry out a coupling reaction. As the bifunctional coupling agent, known ones can be used, and examples thereof include, but are not limited to, alkoxysilane compounds such as trimethoxysilane, triethoxysilane, tetramethoxysilane, tetraethoxysilane, dimethyldimethoxysilane, diethyldimethoxysilane, dichlorodimethoxysilane, dichlorodiethoxysilane, trichloromethoxysilane, and trichloroethoxysilane; dihalogen compounds such as dichloroethane, dibromoethane, dimethyldichlorosilane, and dimethyldibromosilane; and acid esters such as methyl benzoate, ethyl benzoate, phenyl benzoate, and phthalic acid esters. In addition, as the polyfunctional coupling agent having three or more functionalities, conventionally known ones can be used, and are not particularly limited. For example, polyalcohols having three or more functionalities, epoxidized soybean oil, diglycidyl bisphenol A, 1,3-bis(N-N'-diglycidylaminomethyl)cyclohexane and other polyfunctional epoxy compounds; n (wherein R is a hydrocarbon group having 1 to 20 carbon atoms, X is a halogen, and n is an integer of 3 to 4), for example, methylsilyl trichloride, t-butylsilyl trichloride, silicon tetrachloride, and bromides thereof; n (wherein R is a hydrocarbon group having 1 to 20 carbon atoms, X is a halogen, and n is an integer of 3 to 4), for example, polyvalent halogen compounds such as methyltin trichloride, t-butyltin trichloride, and tin tetrachloride. Dimethyl carbonate, diethyl carbonate, and the like may also be used.

[0047] <Denaturation process> The hydrogenated block copolymer (a) used in the fiber of the present embodiment may be a modified block copolymer having an atomic group having a functional group bonded thereto. The atomic group having a functional group is preferably bonded as a pre-step of the hydrogenation step described below. The "atomic group having a functional group" is not limited to the following, but examples thereof include atomic groups containing at least one functional group selected from hydroxyl group, carboxyl group, carbonyl group, thiocarbonyl group, acid halide group, acid anhydride group, carboxylic acid group, thiocarboxylic acid group, aldehyde group, thioaldehyde group, carboxylate group, amide group, sulfonic acid group, sulfonate group, phosphoric acid group, phosphoric acid ester group, amino group, imino group, nitrile group, pyridyl group, quinoline group, epoxy group, thioepoxy group, sulfide group, isocyanate group, isothiocyanate group, silicon halide group, silanol group, alkoxy silicon group, tin halide group, boronic acid group, boron-containing group, boronate base, alkoxy tin group, phenyl tin group, etc. In particular, atomic groups containing at least one functional group selected from hydroxyl group, epoxy group, amino group, silanol group, and alkoxy silane group are preferred. The "atomic group having a functional group" can be bonded by a modifying agent. Examples of the modifying agent include, but are not limited to, tetraglycidyl meta-xylylene diamine, tetraglycidyl-1,3-bisaminomethylcyclohexane, ε-caprolactone, δ-valerolactone, 4-methoxybenzophenone, γ-glycidoxyethyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl dimethylphenoxysilane, bis(γ-glycidoxypropyl)methylpropoxysilane, 1,3-dimethyl-2-imidazolidinone, 1,3-diethyl-2-imidazolidinone, N,N'-dimethylpropylene urea, and N-methylpyrrolidone.

[0048] The modified block copolymer is not particularly limited, but can be obtained, for example, by anionic living polymerization using a polymerization initiator having a functional group or an unsaturated monomer having a functional group, forming a functional group at the living end, or by addition reaction of a modifying agent containing a functional group. Another method for obtaining a modified block copolymer includes reacting a block copolymer with an organic alkali metal compound such as an organolithium compound (metallation reaction), and then subjecting the block polymer to an addition reaction with a modifier having a functional group. However, in the latter method, the hydrogenated block copolymer (a) can be obtained, then subjected to a metallation reaction, and then reacted with a modifying agent to prepare a modified hydrogenated block copolymer. The temperature at which the modification reaction is carried out is preferably 0 to 150° C., more preferably 20 to 120° C. The time required for the modification reaction differs depending on other conditions, but is preferably within 24 hours, more preferably 0.1 to 10 hours. Depending on the type of modifying agent used, the amino group etc. may generally be in the form of an organometallic salt at the stage of reacting with the modifying agent, in which case it can be converted to an amino group etc. by treating with a compound having active hydrogen such as water or alcohol. In such modified block copolymers, a part of the modified block copolymer may be mixed with a block copolymer that is not modified.

[0049] The modified block copolymer may be a secondary modified block copolymer, which is obtained by reacting the modified block copolymer with a secondary modifying agent having reactivity with the functional group of the modified block copolymer. The secondary modifying agent is not particularly limited, but examples thereof include a modifying agent having a functional group selected from a carboxyl group, an acid anhydride group, an isocyanate group, an epoxy group, a silanol group, and an alkoxysilane group, and has at least two functional groups selected from these functional groups. However, when the functional group is an acid anhydride group, it may have one acid anhydride group.

[0050] As described above, when the secondary modifier is reacted with the modified block copolymer, the amount of the secondary modifier used is preferably 0.3 to 10 mol, more preferably 0.4 to 5 mol, and even more preferably 0.5 to 4 mol, per equivalent of the functional group bonded to the modified block copolymer. The method of reacting the modified block copolymer with the secondary modifier is not particularly limited and may be any known method. For example, the melt-kneading method described below and the method of dissolving or dispersing and mixing each component in a solvent or the like and reacting them may be mentioned. It is preferable that these secondary modifications are carried out after the hydrogenation step.

[0051] Suitable secondary modifying agents include, but are not limited to, maleic anhydride, pyromellitic anhydride, 1,2,4,5-benzenetetracarboxylic dianhydride, toluylene diisocyanate, tetraglycidyl-1,3-bisaminomethylcyclohexane, bis-(3-triethoxysilylpropyl)-tetrasulfane, and the like.

[0052] The hydrogenated block copolymer (a) used in the fiber of this embodiment may be a modified block copolymer graft-modified with an α,β-unsaturated carboxylic acid or a derivative thereof, such as an anhydride, ester, amide or imide thereof. Examples of α,β-unsaturated carboxylic acids or derivatives thereof include, but are not limited to, maleic anhydride, maleic anhydride imide, acrylic acid or its ester, methacrylic acid or its ester, endo-cis-bicyclo[2,2,1]-5-heptene-2,3-dicarboxylic acid or its anhydride, and the like. The amount of the α,β-unsaturated carboxylic acid or a derivative thereof added is preferably from 0.01 to 20 parts by mass, and more preferably from 0.1 to 10 parts by mass, per 100 parts by mass of the hydrogenated block copolymer (a). The reaction temperature in the case of graft modification is preferably from 100 to 300°C, more preferably from 120 to 280°C. The method for graft modification is not particularly limited, but for example, the method described in JP-A-62-79211 can be applied.

[0053] <Hydrogenation reaction process> The hydrogenated block copolymer (a) used in the fiber of this embodiment can be obtained by subjecting the above-mentioned non-hydrogenated unmodified or modified block copolymer to a hydrogenation reaction using a specific hydrogenation catalyst. Examples of the hydrogenation catalyst include, but are not limited to, known catalysts: (1) supported heterogeneous hydrogenation catalysts in which a metal such as Ni, Pt, Pd, Ru, etc. is supported on carbon, silica, alumina, diatomaceous earth, etc.; (2) so-called Ziegler-type hydrogenation catalysts which use a transition metal salt such as an organic acid salt or an acetylacetone salt of Ni, Co, Fe, Cr, etc., and a reducing agent such as organoaluminum; and (3) homogeneous hydrogenation catalysts such as so-called organometallic complexes of organometallic compounds such as Ti, Ru, Rh, Zr, etc. In addition, the hydrogenation catalyst is not limited to the following, but for example, hydrogenation catalysts described in JP-B-42-8704, JP-B-43-6636, JP-B-63-4841, JP-B-1-37970, JP-B-1-53851, and JP-B-2-9041 can also be used. Suitable hydrogenation catalysts include titanocene compounds, reducing organometallic compounds, or mixtures thereof. The titanocene compound is not limited to the following, but for example, the compounds described in JP-A-8-109219 can be used. Specific examples include compounds having at least one ligand having a (substituted) cyclopentadienyl skeleton, an indenyl skeleton, or a fluorenyl skeleton, such as biscyclopentadienyl titanium dichloride and monopentamethylcyclopentadienyl titanium trichloride. Examples of the reducing organometallic compound include, but are not limited to, organoalkali metal compounds such as organolithium compounds, organomagnesium compounds, organoaluminum compounds, organoboron compounds, and organozinc compounds.

[0054] The hydrogenation reaction will now be described. In general, the reaction temperature is preferably in the range of 0 to 200°C, more preferably in the range of 30 to 150°C. The pressure of hydrogen used in the hydrogenation reaction is preferably from 0.1 to 15 MPa, more preferably from 0.2 to 10 MPa, and even more preferably from 0.3 to 5 MPa. The hydrogenation reaction time is usually preferably 3 minutes to 10 hours, more preferably 10 minutes to 5 hours. The hydrogenation reaction may be a batch process, a continuous process, or a combination thereof. It is preferable to remove catalyst residues, if necessary, from the solution of the hydrogenated block copolymer obtained through the hydrogenation reaction, and separate the hydrogenated block copolymer from the solution. Examples of the separation method include, but are not limited to, a method in which a polar solvent that is a poor solvent for the hydrogenated modified copolymer, such as acetone or alcohol, is added to the reaction solution after hydrogenation to precipitate and recover the polymer; a method in which the reaction solution is poured into boiling water with stirring and the solvent is removed by steam stripping to recover the polymer; and a method in which the polymer solution is directly heated to distill off the solvent.

[0055] The hydrogenated block copolymer (a) used in the fiber of this embodiment may contain various stabilizers such as phenol-based stabilizers, phosphorus-based stabilizers, sulfur-based stabilizers, and amine-based stabilizers.

[0056] [Method of manufacturing fibers] The fibers of the present embodiment are obtained by melting the hydrogenated block copolymer (a), extruding it from a spinneret of an extruder having a spinneret, and spinning it while cooling it with cold air. Specifically, the hydrogenated block copolymer (a) is fed to a spinning device equipped with a single screw extruder, and melt spun under the conditions of a spinning temperature of 180°C, a die having 12 holes, a hole diameter of 0.35 mm, and a hole length of 0.70 mm, and a take-up speed of 100 m / min. This results in fibers with a single yarn fineness of 10 dtex and a total fineness of 120 dtex.

[0057] [Total fiber fineness] The fibers of the present embodiment preferably have a total fineness of 1 dtex or more and 2000 dtex or less, more preferably 5 to 1000 dtex, and further preferably 10 to 500 dtex. By using the above-mentioned hydrogenated block copolymer (a), good spinnability can be obtained, and by setting the total fineness within the above numerical range, a fiber that is lightweight, has good breathability, and has sufficient strength for practical use can be obtained. The total fiber fineness can be controlled within the above numerical range by adjusting the MFR of the hydrogenated block copolymer, and also by adjusting the extrusion discharge rate, winding speed, and number of holes in the spinneret of the hydrogenated block copolymer.

[0058] [Fiber Uses] The fiber of the present embodiment is particularly excellent in low stress recovery, and is therefore suitable for applications requiring fibers with appropriate elasticity, such as sportswear and cushions. EXAMPLES

[0059] The present invention will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples and comparative examples. The methods for measuring and evaluating physical properties used in the examples and comparative examples are shown below.

[0060] The hydrogenated block copolymers used in the fibers of the Examples and Comparative Examples were subjected to structural identification and physical property measurement as described below.

[0061] [Method of measuring the structure of hydrogenated block copolymer] ((1) Content of total vinyl aromatic monomer units (styrene) in hydrogenated block copolymer (A)) The hydrogenated block copolymer was used to measure the total vinyl aromatic monomer unit (styrene) content using an ultraviolet spectrophotometer (Shimadzu Corporation, UV-2450).

[0062] ((2) Hydrogenation rate of double bonds of conjugated diene monomer units of hydrogenated block copolymer (a)) The hydrogenation rate of the double bonds of the conjugated diene monomer units was measured using the hydrogenated block copolymer with a nuclear magnetic resonance spectrometer (ECS400, manufactured by JEOL RESONANCE).

[0063] ((3) Content of polymer block (a) in hydrogenated block copolymer (a)) The content of the polymer block (a) mainly composed of vinyl aromatic monomer units was measured using a hydrogenated block copolymer by a nuclear magnetic resonance (NMR) apparatus (the method described in Y. Tanaka, et al., RUBBER CHEMISTRY and TECHNOLOGY 54, 685 (1981). Hereinafter, this method will be referred to as the "NMR method").

[0064] ((4) Content of hydrogenated copolymer block (b) in hydrogenated block copolymer (a)) Calculated using the formula: 100 - (content of hydrogenated copolymer block (a) in hydrogenated block copolymer (a)).

[0065] ((5) Amount of vinyl bonds in hydrogenated block copolymer (a)) The amount of vinyl bonds in hydrogenated block copolymers was measured by nuclear magnetic resonance (NMR). The amount of vinyl bonds in the conjugated diene monomer units in the hydrogenated block copolymer was determined from the ratio of the total peak area of ​​1,2-bonds and 3,4-bonds to the total area of ​​all peaks related to the conjugated diene monomer units (the ratio of 1,2-bonds, 3,4-bonds, and 1,4-bonds) among the peaks obtained by NMR measurement.

[0066] ((6) Content of vinyl aromatic monomer units in hydrogenated copolymer block (b) constituting hydrogenated block copolymer (a)) The vinyl aromatic monomer unit content in the hydrogenated copolymer block (b) relative to the entire polymer was calculated from the difference between the total vinyl aromatic monomer unit content in the hydrogenated block copolymer (a) measured in (1) above and the content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (a) measured in (3) above, and the vinyl aromatic monomer unit content in the hydrogenated copolymer block (b) was calculated from the ratio to the content of the hydrogenated copolymer block (b) in the hydrogenated block copolymer (a) measured in (4) above.

[0067] [Method of measuring physical properties of hydrogenated block copolymer] ((1) Hardness) According to JIS K6253, the values ​​at 0 seconds and 15 seconds were measured using a durometer type A and a durometer type D, respectively. After lowering the probe of the hardness tester onto the measurement sample, the hardness values ​​were measured at 0 seconds and 15 seconds. In the table below, the hardness is indicated as hardness (JIS-A, 0 seconds), hardness (JIS-A, 15 seconds), hardness (JIS-D, 0 seconds), and hardness (JIS-D, 15 seconds). Regarding the hardness value, when durometer type D indicates a hardness value of less than 20, the value of durometer type A is used, and when durometer type A indicates a hardness value of more than 90, the value of durometer type D is used. As a guideline, a hardness of 94 on durometer type A corresponds to a hardness of 45 on durometer type D.

[0068] ((2) Melt flow rate (MFR, unit: g / 10 min) The MFR was measured at a temperature of 230° C. and a load of 2.16 kg in accordance with JIS K7210.

[0069] [Measurement of fiber properties] The fibers of the examples and comparative examples were subjected to physical property measurements and characteristic evaluations as described below.

[0070] ((1) Single yarn size) The length and weight of a single yarn were measured with N (number of measurements) = 3, and the average value was calculated in dtex units.

[0071] ((2) Total fineness) The length and weight of the fiber were measured with N (number of measurements) = 3, and the average value was calculated in dtex units. The total fineness was calculated by multiplying the single yarn fineness (1) above by the number of yarns.

[0072] [Evaluation of fiber characteristics] The fibers of the examples and comparative examples were evaluated for their properties as follows.

[0073] ((1) Spinnability, frequency of yarn breakage) The frequency of yarn breakage during fiber spinning was evaluated using the following three-level scale. <Evaluation criteria> ◯: No thread breakage occurs. △: Thread breakage occurs rarely. ×: Thread breakage occurs frequently.

[0074] ((2) Breaking strength) In accordance with the definition of JIS-L1013, the fibers of the examples and comparative examples were left for 24 hours in a temperature and humidity controlled room at 20°C and 65% RH, and then the breaking strength was measured using a tensile tester (Shimadzu Corporation, Autograph DSS-500) with a yarn length of 5 cm, a tensile speed of 50 cm / min, and the number of measurements n=3, and the average value was used.

[0075] ((3) Breaking elongation) In accordance with the definition of JIS-L1013, the fibers of the examples and comparative examples were left for 24 hours in a temperature and humidity controlled room at 20°C and 65% RH, and then the breaking elongation was measured using a tensile tester (Shimadzu Corporation, Autograph DSS-500) with a yarn length of 5 cm, a tensile speed of 50 cm / min, and the number of measurements n=3, and the average value was used.

[0076] ((4) Stress recovery) In accordance with the definition of JIS-L1013, the fibers of the examples and comparative examples were left for 24 hours in a room with temperature and humidity controlled at 20°C and 65% RH, and then, using a tensile tester (Shimadzu Corporation, Autograph DSS-500), they were stretched 200% at a thread length of 5 cm and a pulling speed of 50 cm / min, and then immediately pulled back at a pulling speed of 50 cm / min. This was repeated three times. The elongation of the sample yarn when the stress became 0 after the third pull-back was taken as (L (%)), and the stress recovery (%) was calculated using the following formula. Stress recovery [%] = 100 × (200-L) / (200) The tensile test was performed three times and the average value was calculated. The lower the stress recovery value, the better the stress recovery. 80% or less was considered to be acceptable, and 70% or less was considered to have exhibited better stress recovery.

[0077] The following Tables 1 and 2 show the physical properties of the hydrogenated block copolymer (a), and Tables 3 and 4 show the physical properties and evaluation of the fibers.

[0078] 〔fiber〕 The fibers were produced using the hydrogenated block copolymer (a) described below.

[0079] (Production of hydrogenated block copolymer (a)) <Preparation of hydrogenation catalyst> In the examples and comparative examples described later, the hydrogenation catalyst used in producing the hydrogenated block copolymer was prepared by the following method. A reaction vessel equipped with a stirrer was purged with nitrogen and charged with 1 liter of dried and purified cyclohexane. Next, 100 mmol of bis(η5-cyclopentadienyl)titanium dichloride was added. While thoroughly stirring the mixture, an n-hexane solution containing 200 mmol of trimethylaluminum was added and the mixture was allowed to react at room temperature for about 3 days to obtain a hydrogenation catalyst.

[0080] <Production Example 1: Hydrogenated Block Copolymer (a)-1> Batch polymerization was carried out using a tank-type reactor (internal volume: 10 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 15 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.115 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.9 mol of N,N,N',N'-tetramethylethylenediamine (hereinafter referred to as "TMEDA") per 1 mol of n-butyllithium were added and polymerized at 65°C for 1 hour. Next, a cyclohexane solution (concentration 20% by mass) containing 29 parts by mass of butadiene and 41 parts by mass of styrene was added and polymerized for 2 hours at 80° C. Finally, a cyclohexane solution (concentration 20% by mass) containing 15 parts by mass of styrene was added and polymerized for 1 hour at 65° C. Thereafter, methanol was added to terminate the polymerization reaction. The block copolymer obtained as described above had a styrene content of 71 mass %, a polystyrene block content of 30 mass %, a vinyl bond amount of 22 mass %, and a weight average molecular weight of 65,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting block copolymer in an amount of 100 ppm (Ti standard) per 100 parts by mass of the block copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 65°C. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the block copolymer to obtain a hydrogenated block copolymer (a)-1. The hydrogenation rate of the resulting hydrogenated block copolymer (a)-1 was 98%. Other physical properties are shown in Table 1.

[0081] <Production Examples 2 to 7: Hydrogenated Block Copolymers (A)-2 to 7, Production Examples A to C: (A)-A to C> In the method for producing the hydrogenated block copolymer (a)-1, the polymerization method and hydrogenation conditions were adjusted to produce (a)-2 to (a)-7 and (a)-A to (a)-C. These physical properties are shown in Tables 1 and 2 below.

[0082] [Manufacturing of Fibers] Example 1 The hydrogenated block copolymer (a)-1 was fed to a spinning apparatus equipped with a single screw extruder, and melt spun at a spinning temperature of 180°C, using a die having 12 holes, a hole diameter of 0.35 mm, and a hole length of 0.70 mm, and at a take-up speed of 100 m / min, to obtain a fiber having a single fiber fineness of 10 dtex and a total fineness of 120 dtex. The elastic yarn of the hydrogenated block copolymer (a)-1 thus obtained had a breaking strength of 0.77 (cN / dt) and a breaking elongation of 258%.

[0083] (Examples 2 to 9), (Comparative Examples 1 to 3) In Examples 2 to 7 and Comparative Examples 1 to 3, the production conditions were not changed and only the type of hydrogenated block copolymer (a) was changed to produce fibers. In Examples 8 and 9, fibers with different total finenesses were obtained by changing the single hole discharge amount and the winding speed.

[0084] In the following Tables 1 to 4, "-" indicates that no measurement was performed.

[0085] [Table 1]

[0086] [Table 2]

[0087] [Table 3]

[0088] [Table 4] [Industrial Applicability]

[0089] INDUSTRIAL APPLICABILITY The fiber of the present invention has industrial applicability in the fields of clothing such as sportswear, interior materials such as cushions, and the like.

Claims

1. A fiber containing a hydrogenated block copolymer (a) that satisfies the following conditions (1) to (4): <Condition (1)>: The hydrogenated block copolymer (a) is a hydrogenated product of a block copolymer containing vinyl aromatic monomer units and conjugated diene monomer units. <Condition (2)>: The hydrogenated block copolymer (a) contains at least one polymer block (a) mainly composed of a vinyl aromatic monomer unit, The content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (i) is 10% by mass or more. <Condition (3)>: The hydrogenated block copolymer (a) contains at least one hydrogenated copolymer block (b) composed of a vinyl aromatic monomer unit and a conjugated diene monomer unit, The content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is from 5% by mass to 79% by mass. <Condition (4)>: The hydrogenated block copolymer (a) has an MFR value of 10 or more as measured in accordance with JIS K7210 under conditions of a temperature of 230° C. and a load of 2.16 kg.

2. The total fineness is 10 dtex or more and 500 dtex or less. The fiber of claim 1.

3. The content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is 45% by mass or more and 79% by mass or less. The fiber of claim 1.

4. the content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (i) is 15% by mass or more and 40% by mass or less; The fiber of claim 1.

5. The hydrogenated block copolymer (a) has an MFR value of 50 or more, as measured in accordance with JIS K7210 under conditions of a temperature of 230° C. and a load of 2.16 kg. The fiber of claim 1.

6. The hydrogenated block copolymer (a) is The instantaneous hardness measured with a durometer type A according to JIS K6253 is 60 or more, The instantaneous hardness measured with a durometer type D according to JIS K6253 is 50 or less. The fiber of claim 1.

7. The fiber is a fiber for any application selected from the group consisting of sportswear and cushions. The fiber of claim 1.

8. A method for producing the fiber according to any one of claims 1 to 7, comprising the steps of: The hydrogenated block copolymer (a) is melted, extruded from a spinneret of an extruder having a spinneret, and spun while being cooled with cold air. A method for producing fibers.

Citation Information

Patent Citations

  • Composition for treatment due to melt spining or melt blowing

    JP1987033818A

  • Fiber composed of hydrogenated block copolymer

    JP1994057525A